Association of statin use with clinical outcomes in patients with triple‐negative breast cancer. Issue 22 (3rd August 2021) - Nowakowska, Malgorzata K.; Lei, Xiudong; Thompson, Mikayla T.; Shaitelman, Simona F.; Wehner, Mackenzie R.; Woodward, Wendy A.; Giordano, Sharon H.; Nead, Kevin T.
Abstract : Background: Previous studies have examined the association of statin therapy and breast cancer outcomes with mixed results. The objective of this study was to investigate the clinical effects of incident statin use among individuals with triple‐negative breast cancer (TNBC). Methods: Data from the Surveillance, Epidemiology, and End Results‐Medicare and Texas Cancer Registry‐Medicare databases were used, and women aged ≥66 years who had stage I, II, and III breast cancer were identified. Multivariable Cox proportional hazards regression models were used to examine the association of new statin use in the 12 months after a breast cancer diagnosis with overall survival (OS) and breast cancer‐specific survival (BCSS). Results: When examining incident statin use, defined as the initiation of statin therapy in the 12 months after breast cancer diagnosis, a significant association was observed between statin use and improved BCSS (standardized hazard ratio, 0.42; 95% confidence interval [CI], 0.20‐0.88; P = .022) and OS (hazard ratio, 0.70; 95% CI, 0.50‐0.99; P = .046) among patients with TNBC (n = 1534). No association was observed with BCSS (standardized hazard ratio, 0.99; 95% CI, 0.71‐1.39; P = .97) or OS (hazard ratio, 1.04; 95% CI, 0.92‐1.17; P = .55) among those without TNBC (n = 15, 979). The results were consistent when examining statin exposure as a time‐varying variable. Conclusions: Among women with I, II, and III TNBC, initiation of statin therapy in the 12 months after breast cancer diagnosis was associated with an OS and BCSS benefit. Statins may have a role in select patients with breast cancer, and further investigation is warranted. Abstract : Statins have been shown to target pathways related to breast cancer carcinogenesis, particularly in aggressive subtypes like triple‐negative breast cancer. A statistically significant association is reported between clinical outcomes and incident statin use in patients with triple‐negative breast cancer in a large sample of patients from the Surveillance, Epidemiology, and End Results‐Medicare database.